The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0482-50042007000100005
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco associados à osteoporose em uma população de mulheres brasileiras residentes em São José do Rio Pardo, estado de São Paulo

Abstract: Objectives: to assess the main risk factors associated to low bone mass and to propose algorithms for the indication of the evaluation of bone mineral density in a women population from São José do Rio Pardo, state of São Paulo. Methods: 324 women (mean age 60 years old) were studied. A questionnaire was sent by regular mail to collect data for several osteoporosis risk factors, as well as both personal and mother's history of fractures. Bone mineral density was measured using DXA, measuring the lumbar spine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“…The anthropometric variables did not show any association with bone mass in our study, but Parisi Júnior et al evaluated 314 women with an average age of 60.2 ± 9.96 years and observed that those with a mean BMI of 25.82 ± 4.33 kg/ had low bone mass, those with a mean BMI of 25.34 ± 3.85 kg/m 2 had osteoporosis and those with a mean BMI of 27.02 ± 4.98 kg/m 2 had normal bone mass, although bone mass was evaluated by means of bone mineral densitometry using dual energy x-ray absorptiometer (DEXA). 41 In the study conducted by Steiner et al, in which the risk of osteoporosis among 461 women of mean age of 60 ± 9.0 was evaluated by means of calcaneal ultrasound, a positive relationship was observed between bone mass and BMI (P = 0.006): women with BMI of 29.1 ± 4.9 kg/m 2 presented low risk of osteoporosis; those with BMI of 27.3 ± 4.5 kg/m 2 presented an average risk and women with a BMI of 26.9 ± 6.0 kg/m 2 presented high risk. 39 Thus, these studies suggest that higher BMI may provide a protective effect, regardless of the methodology used for evaluating bone mass.…”
Section: Introductionmentioning
confidence: 99%
“…The anthropometric variables did not show any association with bone mass in our study, but Parisi Júnior et al evaluated 314 women with an average age of 60.2 ± 9.96 years and observed that those with a mean BMI of 25.82 ± 4.33 kg/ had low bone mass, those with a mean BMI of 25.34 ± 3.85 kg/m 2 had osteoporosis and those with a mean BMI of 27.02 ± 4.98 kg/m 2 had normal bone mass, although bone mass was evaluated by means of bone mineral densitometry using dual energy x-ray absorptiometer (DEXA). 41 In the study conducted by Steiner et al, in which the risk of osteoporosis among 461 women of mean age of 60 ± 9.0 was evaluated by means of calcaneal ultrasound, a positive relationship was observed between bone mass and BMI (P = 0.006): women with BMI of 29.1 ± 4.9 kg/m 2 presented low risk of osteoporosis; those with BMI of 27.3 ± 4.5 kg/m 2 presented an average risk and women with a BMI of 26.9 ± 6.0 kg/m 2 presented high risk. 39 Thus, these studies suggest that higher BMI may provide a protective effect, regardless of the methodology used for evaluating bone mass.…”
Section: Introductionmentioning
confidence: 99%
“…A fragilidade é uma síndrome biológica de redução multissistêmica da capacidade fisiológica do idoso, caracterizada por diminuição das reservas e menor resistência a estresse. Os sinais dessa síndrome são, entre outros, diminuição da força muscular, diminuição de atividade física, e menor taxa metabólica (35,36).…”
Section: Discussionunclassified
“…Também a associação do evento -uso das duas mãos para passar da posição sentada para a posição em pé -com a presença de diagnóstico de neoplasias pode ser compreendida em função da fragilidade biológica que se relaciona a essa categoria de enfermidades crônicas (35).…”
Section: Discussionunclassified